Raising healthy teenagers equipping your child to navigate the pitfalls and dangers of teen life - Kersting, Thomas 1972- (Grand Rapids, Michigan Baker Books, a division of Baker Publishing Group, 2023)
Family therapist and renowned parenting expert unpacks the unique challenges teens face today-including isolation from friends and family, increased screen time, and a steady stream of fear-based media-and helps parents guide them toward better mental health and life success"--Provided by publisher.
Includes bibliographical references.
Keywords: Parent and teenager; Parenting -- Psychological aspects; Adolescent psychology